Social networking communities and e-dating services [ concepts and implications - Romm-Livermore, Celia , 1954-; Setzekorn, Kristina (Information Science Reference, 2009)
"This book provides an overview of the major questions that researchers and practitioners in this area are addressing at this time and by outlining the possible future directions for theory development and empirical research on social networking and eDating"--Provided by publisher.